2018
DOI: 10.1109/lgrs.2017.2779559
|View full text |Cite
|
Sign up to set email alerts
|

Development and Assessment of a Data Set Containing Frame Images and Dense Airborne Laser Scanning Point Clouds

Abstract: This letter describes the main features of a data set that contains aerial images acquired with a medium format digital camera and point clouds collected using an airborne laser scanning unit, as well as ground control points and direct georeferencing data. The flights were performed in 2014 over an urban area in Presidente Prudente, São Paulo, Brazil, using different flight heights. These flights covered several features of interest for research, including buildings of different sizes and roof materials, road… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…The selected study area shown in Figure 2 consists of a small portion of the urban region of Presidente Prudente/Brazil. The LiDAR dataset was acquired with a RIEGL LMS Q680i in 2014 by Sensormap Geotecnologia, a subsidiary company of the Engemap Group (Tommaselli et al, 2018). The point cloud has 1.65 million points and covers an area of 428 m by 351 m, resulting in a average point density of 10.9 pts/m 2 .…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected study area shown in Figure 2 consists of a small portion of the urban region of Presidente Prudente/Brazil. The LiDAR dataset was acquired with a RIEGL LMS Q680i in 2014 by Sensormap Geotecnologia, a subsidiary company of the Engemap Group (Tommaselli et al, 2018). The point cloud has 1.65 million points and covers an area of 428 m by 351 m, resulting in a average point density of 10.9 pts/m 2 .…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The point cloud has 1.65 million points and covers an area of 428 m by 351 m, resulting in a average point density of 10.9 pts/m 2 . According to Tommaselli et al (2018), the average flying height was 550 m, and the point cloud has a 12 cm vertical root mean square error (RMSE), which was assessed using ground control points (GCPs) tracked with double frequency GNSS receivers. This point cloud has a considerable ground elevation difference of about 30 m. In addition, the region contains several objects that are easily mistaken as positive outliers, such as light poles, power transmission lines, and low density sampling on building walls.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…This section presents the experiments and results obtained using the proposed method. The experiments were performed considering a LiDAR dataset acquired over the city of Presidente Prudente/Brazil by the company Sensormap Geotecnologia, which belongs to the Engemap Group, as can be seen in Tommaselli et al (2018). The data set was acquired from a flight height of 900 m with an average density of 5 points/m 2 .…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The experiments were performed considering two LiDAR datasets. The first dataset is part of the Unesp Photogrammetric Data Set and was generated from three different flying heights over Presidente Prudente/Brazil (Tommaselli et al, 2018). This paper considers only the lowest flight.…”
Section: Lidar Datasetmentioning
confidence: 99%